Non-unitary quantum electronics: Novel functions from the edge of the quantum world. (22nd March 2021) - Mannhart, J; Boschker, H; Bredol, P
Abstract: Novel categories of electronic devices and quantum materials are obtained by pipelining the unitary evolution of electron quantum states as described by Schrödinger's equation with non-unitary processes that interrupt the coherent propagation of electrons. These devices and materials reside in the fascinating transition regime between quantum mechanics and classical physics. The devices are designed such that a nonreciprocal unitary state evolution, achieved by means of a broken inversion symmetry, is interrupted by individual inelastic scattering events caused by defects coupled to an environment. Two-terminal non-unitary quantum devices, for example, feature nonreciprocal conductance in linear response. Thus, they are exemptions to Onsager's reciprocal relation, and they challenge the second law of thermodynamics. Furthermore, materials and metamaterials featuring such functionalities may be realized by embedding such nanostructures into their unit cells.